DX5+CD4+ T cells modulate CD4+ T‐cell response via inhibition of IL‐12 production by DCs. Issue 2 (14th February 2013) - el Bannoudi, Hanane; Han, Wanda G. H.; Stoop, Jeroen N.; Louis‐Plence, Pascale; Huizinga, Tom W. J.; Toes, René E. M.
<x xml:space="preserve">Abstract</x> DX5+CD4+ T cells have been shown to dampen collagen‐induced arthritis and delayed‐type hypersensitivity reactions in mice. These cells are also potent modulators of T‐helper cell responses through direct effects on CD4+ T cells in an IL‐4 dependent manner. To further characterize this T‐cell population, we studied their effect on DCs and the potential consequences on T‐cell activation. Here, we show that mouse DX5+CD4+ T cells modulate DCs by robustly inhibiting IL‐12 production. This modulation is IL‐10 dependent and does not require cell contact. Furthermore, DX5+CD4+ T cells modulate the surface phenotype of LPS‐matured DCs. DCs modulated by DX5+CD4+ T‐cell supernatant express high levels of the co‐inhibitor molecules PDL‐1 and PDL‐2. OVA‐specific CD4+ T cells primed with DCs exposed to DX5+CD4+ T‐cell supernatant produce less IFN‐γ than CD4+ T cells primed by DCs exposed to either medium or DX5−CD4+ T‐cell supernatant. The addition of IL‐12 to the co‐culture with DX5+ DCs restores IFN‐γ production. When IL‐10 present in the DX5+CD4+ T‐cell supernatant is blocked, DCs re‐establish their ability to produce IL‐12 and to efficiently prime CD4+ T cells. These data show that DX5+CD4+ T cells can indirectly affect the outcome of the T‐cell response by inducing DCs that have poor Th1 stimulatory function.